2009
DOI: 10.1074/jbc.m807228200
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Raft Segregation Modulates TRPM8 Channel Activity

Abstract: Transient receptor potential channels are a family of cation channels involved in diverse cellular functions. Most of these channels are expressed in the nervous system and play a key role in sensory physiology. TRPM8 (transient receptor potential melastatine 8), a member of this family, is activated by cold, cooling substances such menthol and icilin and voltage. Although TRPM8 is a thermosensitive channel highly expressed in cold sensory neurons, the mechanisms underlying its temperature sensitivity are stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 50 publications
8
114
0
Order By: Relevance
“…Equal amounts of protein for each condition (15-30 g) were denatured at 95°C for 5 min, loaded onto a 7.5% SDS-polyacrylamide gel, and electrophoresed. Proteins were transferred to a nitrocellulose membrane, blocked with 10% skim milk in TBS, and incubated with antibodies against mouse TRPM8 (diluted 1:500) (14). Horseradish peroxidase (HRP)-coupled anti-rabbit secondary antibodies (Sigma) were used at a final concentration of 1:2000 for detection, and the signal was developed with an enhanced chemiluminescence kit (Amersham Biosciences) and recorded by using an image analyzer LAS-1000Plus (Fujifilm).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Equal amounts of protein for each condition (15-30 g) were denatured at 95°C for 5 min, loaded onto a 7.5% SDS-polyacrylamide gel, and electrophoresed. Proteins were transferred to a nitrocellulose membrane, blocked with 10% skim milk in TBS, and incubated with antibodies against mouse TRPM8 (diluted 1:500) (14). Horseradish peroxidase (HRP)-coupled anti-rabbit secondary antibodies (Sigma) were used at a final concentration of 1:2000 for detection, and the signal was developed with an enhanced chemiluminescence kit (Amersham Biosciences) and recorded by using an image analyzer LAS-1000Plus (Fujifilm).…”
Section: Methodsmentioning
confidence: 99%
“…Studies in dorsal root ganglia neurons also confirmed that endogenous TRPM8 channels are highly glycosylated in vivo (14). To further study the N-glycosylation of TRPM8 in a native context, we cultured TG neurons that express TRPM8 endogenously and analyzed their immunoreactive profile to TRPM8.…”
Section: Trpm8mentioning
confidence: 99%
See 3 more Smart Citations